Parental Report of Gender Differences in Sexual Functioning among Adolescents with Down Syndrome: A Jordanian Experience - Amr, Mostafa; FW Zaki, Nevin; Raddad, Dahoud; Zayed, Zayed; Deba, Mohamed; Hassan, Moussa; Hasan, Naim (Journal of Behavior Therapy And Mental Health, 2016)
Background: Recently, there has been an increased interest in sexuality among teenagers with Down syndrome (DS). Although DS has been well studied in the western continents, its research is relatively scarce in the Arab region. Aims: This is a cross -sectional study to explore the demographic characteristics and the sexual profile among 23 adolescents with DS who attended the outpatient psychiatric clinic of a tertiary care hospital in Amman, Jordan. Method: A semi-structured interview conducted with the parents of individuals with DS was used to record the socio-demographic profile, self-care skills, socio-sexual skills and sexual behavior. Results: The mean age of the sample was 13.5 years, out of which 69% were males; 26% were sexually oriented and able to identify their gender identity. When questioned about masturbation and self-care skills, a significant statistical difference was observed where girls showed more self-care skills while boys showed more masturbation acts. The p- value was (p = 0.045) for masturbation, p = 0.02 for washing the genitals, p = 0.011 for changing the underwear, and p = 0.001 for hygiene after using the toilet. Conclusion: The present study expands our knowledge about sexual issues in individuals with DS. We found that all adolescents reported adaptation to the physical changes of puberty. However, gender difference on some of the sexuality subscales was observed, mainly in the practice of some self- care, socio-sexual skills and sexual behavior.
Keywords: Down syndrome; Sexuality: Gender; Jordan